Nosocomial outbreak of monoclonal VIM carbapenemase-producing Enterobacter cloacae complex in an intensive care unit during the COVID-19 pandemic: an integrated approach. (February 2022) - Mullié, C.; Lemonnier, D.; Adjidé, C.C.; Maizel, J.; Mismacque, G.; Cappe, A.; Carles, T.; Pierson-Marchandise, M.; Zerbib, Y.
Summary: Background: An outbreak of VIM carbapenemase-expressing Enterobacter cloacae complex occurred between March and October 2020 in an intensive care unit (ICU) of a tertiary care and teaching hospital in France. At the same time, the hospital was facing the COVID-19 first wave. Aim: To describe the management of an outbreak caused by a VIM-producing Enterobacter cloacae complex strain during the COVID-19 pandemic in an ICU and to show the importance of an integrated approach. Methods: A multi-focal investigation was conducted including descriptive and molecular epidemiology, environmental screening, and assessment of infection prevention and control measures. Findings: A total of 14 cases were identified in this outbreak with a high attributable mortality rate (85.7%). The outbreak management was coordinated by a crisis cell, and involved the implementation of multi-disciplinary actions such as: enhanced hygiene measures, microbiological and molecular analysis of patients and environmental E. cloacae complex strains, and simulation-based teaching. All 23 E. cloacae complex strains isolated from patients and environment samples belonged to multi-locus sequence type ST78 and carried bla -VIM4 gene. Using Fourier transform infrared spectroscopy, all but two isolates were also found to belong to a single cluster. Although the source of this outbreak could not be pinpointed, the spread of the strain was controlled thanks to this multi-focal approach and multi-disciplinary implementation. Conclusion: This investigation highlighted the usefulness of Fourier transform infra-red spectroscopy in the rapid typing of outbreak strains as well as the importance of an integrated approach to successfully fight against multidrug-resistant micro-organism dissemination and healthcare-associated infections.